2020
DOI: 10.3389/fonc.2020.582863
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Downregulates Expression of PD-1/PD-L1 and Infiltration of CD8+ T Cells by Inhibiting IL-17 Signaling Transduction in Breast Cancer

Abstract: Background: The relationship between the interleukin 17 (IL-17) family of cytokines and breast cancer has been widely studied in recent years. Many studies have revealed increased levels of the cytokine IL-17A in estrogen receptor (ER)-negative or triple-negative breast cancer. Upregulation of IL-17A signaling is associated with increased expression of programmed cell death protein 1 (PD-1) and programmed death-ligand 1 (PD-L1) in breast cancer with low ER expression and may elevate the infiltration of CD8 + T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 46 publications
0
37
1
Order By: Relevance
“…Additionally, we studied the relationship between HIF1α, IL17A, and CXCL10 and immune microenvironment of BC. It is well known that TNBC and HER2+ BC are more tightly related to immune response ( Shuai et al, 2020 ), so we primarily analyzed the association of these three genes with several immune cell subsets (CD4+ T cell, CD8+ T cell, neutrophil, dendritic cell, and macrophage) in TNBC and HER2+ BC population. Among these immune cells, only infiltration of neutrophils was positively correlated with HIF1α, IL17A, and CXCL10 expression, while other types of immune cells were weakly related to these three genes ( Figures 6A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we studied the relationship between HIF1α, IL17A, and CXCL10 and immune microenvironment of BC. It is well known that TNBC and HER2+ BC are more tightly related to immune response ( Shuai et al, 2020 ), so we primarily analyzed the association of these three genes with several immune cell subsets (CD4+ T cell, CD8+ T cell, neutrophil, dendritic cell, and macrophage) in TNBC and HER2+ BC population. Among these immune cells, only infiltration of neutrophils was positively correlated with HIF1α, IL17A, and CXCL10 expression, while other types of immune cells were weakly related to these three genes ( Figures 6A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it has been thought that the upregulation of PD-L1 in tumor cells (a rare phenomenon in BC) could be related to tumor immune evasion [61,111]. PD-L1 mRNA was found to be expressed in at least 20% of BC cells [112] and the majority of tumors that upregulated PD-L1 are HR− (52% vs. 48%) [112,113]. Many studies have relatively consistently reported that PD-L1 represents a good survival prognostic factor in TNBC [114][115][116][117][118][119], whereas the clinical role of PD-L1 is not clear in HR+ patients [61].…”
Section: Highlights Of Pd1/pd-l1 and Hr+ Bcmentioning
confidence: 99%
“…IL-17E acted as an antagonist of IL-17 pathway by suppressing the activation function of IL-17A, IL-17C, and IL-17F. The inhibition of ER-induced IL-17 signaling decreases the expression level of PD-L1 in ER + breast cancer, which reveals the essential role of IL-17 in ER-induced PD-L1 expression decrease [ 64 ].…”
Section: Cancer Cellmentioning
confidence: 99%